The Use of Immersive Virtual Reality in Sensory Sessions on an Older Peoples Mental Health Ward: Service Evaluation of Feasibility and Acceptability - Ciju Benjamin; Felix Clay (BJPsych Open)
Aims: Immersive virtual reality has the potential to give people admitted on inpatient ward settings a break from these limited environments. This service evaluation reviewed the use of immersive virtual reality relaxation activities as a part of routine occupational therapy sensory sessions in an older people’s inpatient mental health ward for dementia and functional conditions. We assessed acceptability and feasibility by reviewing user experience and therapeutic engagement in terms of relaxation, engagement and interaction.